PENGARUH FRAKSI VOLUME DAN PEMBEBANAN TERHADAP SIFAT FISIK DAN MEKANIK KOMPOSIT BERPENGUAT SERBUK CANGKANG KERANG LOKAN - Hestiawan, Hendri; FA, A. Sofwan; Amri, Khairul; Farid, Muhammad (Universitas Muhammadiyah Metro, 2024)
The increasing consumption of local clam shells which contain high nutritional value in society has resulted in an increase in waste sea shells in areas around the coast of Bengkulu Province. The high calcium content in lokan clam shells attracts researchers to study the physical and mechanical properties of epoxy resin composites reinforced lokan clam shell powder. This research aims to investigate the effect of variations in the volume fraction of lokan clam shell powder and the mold loading on the physical and mechanical properties of composites reinforced lokan clam shell powder. The process of manufacturing shell powder is carried out by heating at a temperature of 900oC for 6 hours. Variations in the volume fraction of lokan clam shell powder consist of 30, 50, 70%. Meanwhile, the mold loading was varied by 0, 500 N, and 1 kN. The manufacturing process uses hand lay-up techniques. Physical and mechanical tests on composites include water absorption tests, density, tensile tests and impact tests. The results of the research show that the powder volume fraction and mold loading influence the physical and mechanical properties of composites reinforced lokan clam shell powder. The best physical properties of composite were obtained at a powder volume fraction of 70% and a mold loading of 1 kN, namely with a density of 1.43 g/cm3. The best mechanical properties of composite were obtained at a volume fraction of 30% and a mold loading of 1 kN, namely with a tensile strength of 33.2 MPa and an impact toughness of 366.8 kJ/m2.